Impacts of farming activities on carbon deposition based on fine soil subtype classification - Wang, Qiuju; Zhang, Dongdong; Jiao, Feng; Zhang, Haibin; Guo, Zhenhua (Frontiers in Plant Science, 2024)
Soil has the highest carbon sink storage in terrestrial ecosystems but human farming activities affect soil carbon deposition. In this study, land cultivated for 70 years was selected. The premise of the experiment was that the soil could be finely categorized by subtype classification. We consider that farming activities affect the soil bacterial community and soil organic carbon (SOC) deposition differently in the three subtypes of albic black soils. Ninety soil samples were collected and the soil bacterial community structure was analysed by high-throughput sequencing. Relative changes in SOC were explored and SOC content was analysed in association with bacterial concentrations. The results showed that the effects of farming activities on SOC deposition and soil bacterial communities differed among the soil subtypes. Carbohydrate organic carbon (COC) concentrations were significantly higher in the gleying subtype than in the typical and meadow subtypes. RB41, Candidatus-Omnitrophus and Ahniella were positively correlated with total organic carbon (TOC) in gleying shallow albic black soil. Corn soybean rotation have a positive effect on the deposition of soil carbon sinks in terrestrial ecosystems. The results of the present study provide a reference for rational land use to maintain sustainable development and also for the carbon cycle of the earth.